Total lesion glycolysis of primary tumor and lymphnodes is a strong predictor for development of distant metastases in oropharyngeal carcinoma patients with independent validation in automatically delineated lesions - Sebastian Zschaeck; Marina Hajiyianni; Patrick Hausmann; Pavel Nikulin; Emily Kukuk; Christian Furth; Paulina Cegla; Elia Lombardo; Joanna Kazmierska; Adrien Holzgreve; Iosif Strouthos; Carmen Stromberger; et al. (Cancer Imaging)
Abstract Background Oropharyngeal carcinomas are characterized by an increasing incidence and a relatively good prognosis. Nonetheless, a considerable number of patients develops metachronous distant metastases; identification of these patients is an urgent medical need. Methods This is a retrospective multicenter evaluation of 431 patients. All patients underwent [18F]-FDG positron emission tomography (PET). The cohort was split into an explorative group (n = 366) and a validation group (n = 65). Lesions were manually delineated in the explorative group and automatically delineated by a convolutional neuronal network (CNN) in the validation group. Quantitative PET parameters standardized uptake value (SUV), metabolic tumor volume (MTV), and total lesion glycolysis (TLG) were calculated for primary tumors (prim) and tumor plus lymphnodes (all). Association of parameters with freedom from distant metastases (FFDM) and overall survival (OS) was tested by cox regression analyses. Results In the explorative group, univariate analyses revealed an association of metric MTVprim (p = 0.022), MTVall (p < 0.001) and TLGall (p < 0.001) with FFDM, binarized parameters were also associated with FFDM (p < 0.001 and p = 0.002). Bootstrap analyses revealed a significantly better association of TLGall compared to TLGprim with FFDM (p = 0.02). MTVall and TLGall remained significantly associated with FFDM upon multivariate testing (p = 0.002, p = 0.031, respectively). In the validation group, the cutoff value for TLGall but not for TLGprim was significantly associated with FFDM (HR = 3.1, p = 0.045). Additional analyses with manually delineated contours of the validation cohort revealed a similar effect (HR = 3.47, p = 0.026). No considerable differences between HPV positive and negative disease were observed. Conclusions TLGall is a promising biomarker to select OPC patients with high risk for metachronous distant metastases.